Early aetiological agent identification of osteomyelitis with the Light Cycler SeptiFast test from peripheral blood. (28th November 2013) - Pasticci, Maria Bruna; Rinonapoli, Giuseppe; Leli, Christian; Mencacci, Antonella
Abstract : The commercial real-time PCR Septi Fast test allows identification of 25 bacterial and fungal species directly from peripheral blood in patients with bloodstream infections. A 22-year-old Caucasian woman reported an open femur fracture requiring a two step surgical procedure. After the second procedure the patient manifested sepsis and Enterobacter cloacae/aerogenes DNA was detected in the peripheral blood with the Septi Fast . Thereafter, femur osteomyelitis was diagnosed and E cloacae was cultured from intraoperative bone samples. The patient completed a 3-month course of antimicrobial therapy. Five months after therapy was discontinued, the patient remained symptom free, but delayed bone consolidation occurs. Molecular methods to identify aetiological agents in blood, in addition to conventional cultures, could represent an advantageous tool in clinical practice also in patients with post-traumatic bone infections.